Technical Review of Developments in Endoscopic Ultrasound-Guided Hepaticogastrostomy - Takeshi Ogura; Kazuhide Higuchi (Korean Society of Gastrointestinal Endoscopy, 2021)
Endoscopic ultrasound-guided biliary drainage has been developed as an alternative method for biliary drainage. EUS-guided hepaticogastrostomy (EUS-HGS) can be attempted via the trans-gastric route. These procedures are technically complex for two reasons. First, puncture of the intrahepatic bile duct via the trans-gastric route can be more difficult than that by other approaches because of the small diameter of the target site, and guidewire insertion or manipulation is challenging during EUS-HGS. Second, critical adverse events, such as stent migration into the abdominal cavity, could occur because of the greater mobility of the stomach compared to the duodenum. Therefore, endoscopists should be cautious when performing EUS-HGS. An advantage of EUS-HGS is that it can be performed in patients with complications such as duodenal bulb obstruction or surgically altered anatomy. Recent advances in technique and improvements in devices and stents for EUS-HGS have shown promise for improving the technical success rate of EUS-HGS and reducing the rate of adverse events. However, endoscopists should remain aware of the possibility of critical adverse events such as stent migration.